THE EFFECTIVENESS OF USING GEOGEBRA MEDIA IN ENHANCING NUMERACY LITERACY OF GRADE VIII STUDENTS ON THE TOPIC OF SYSTEMS OF TWO-VARIABLE LINEAR EQUATIONS (SPLDV) - Aulia, Gina Putri; Karimah, Kasyifatul; Syahdi, Fahmi; Rosita, Cita Dwi; Karimah, Nurul Ikhsan (Jurnal Pendidikan Matematika dan IPA, 2026)
Numeracy literacy refers to the understanding and skills in applying various numbers and symbols related to basic mathematics to solve practical problems in everyday situations. Numeracy skills are essential as they are closely connected to daily life. The benefits of numeracy literacy, as directly experienced by students, include the ability and competence in handling symbols and calculations applicable in real-life contexts, such as effective task management and making decisions with ease. This study aims to analyze the effectiveness of GeoGebra as a learning medium in improving students’ numeracy literacy on the topic of Systems of Two-Variable Linear Equations (SPLDV), with attention to students’ abilities to understand concepts, use mathematical representations, and solve contextual problems. The study employed a quasi-experimental design involving 29 Grade VIII students, using a one-group pretest-posttest design. Research instruments consisted of a questionnaire to measure students’ responses to GeoGebra and six essay questions related to SPLDV. Following the administration of the pretest, posttest, and questionnaire, the data were analyzed to determine students’ test score improvements using the Paired Samples T-Test and N-Gain calculations. The Paired Samples T-Test results showed an average pretest-posttest difference of 22.74 with a calculated t-value of 5.523, yielding a significance level of